2023
DOI: 10.13189/saj.2023.110104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Several Factors that Affect the Learning Outcomes of Physical Education

Abstract: Success in learning Physical Education (PE)is a benchmark for students to apply health values throughout their lives. Therefore, this study aims to investigate and evaluate factors related to the achievement of PE learning outcomes, namely Body Mass Index (BMI), Physical Fitness (PF), and learning motivation. A total of 75 male students from Madrasah Tsanawiyah (junior high school) in the city of Padang, West Sumatra, Indonesia participated in this study. Characteristics of the participants were grade eight ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…This tool is an innovation in sports technology for collecting data in sports involving hand-eye coordination (such as volleyball, badminton, tennis, basketball, hockey, martial arts and other sports where hands are dominant). This includes game sports in physical education as well (Firdaus et al, 2023;Umar, Alnedral, Ihsan, Mario, & Mardesia, 2023;Welis, Yendrizal, Darni, & Mario, 2023). Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This tool is an innovation in sports technology for collecting data in sports involving hand-eye coordination (such as volleyball, badminton, tennis, basketball, hockey, martial arts and other sports where hands are dominant). This includes game sports in physical education as well (Firdaus et al, 2023;Umar, Alnedral, Ihsan, Mario, & Mardesia, 2023;Welis, Yendrizal, Darni, & Mario, 2023). Previous studies reported that technology in the sports sector is a complex system for collecting and processing large amounts of data (Camomilla, Bergamini, Fantozzi, & Vannozzi, 2018;Ratten, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Protein supplementation will only produce muscle strength with carefully planned, structured, and prolonged weight training. According to previous research, effective sports training must be planned and programmed (Antara et al, 2023;Firdaus et al, 2023;Umar et al, 2023;Welis et al, 2023). In weight training, it is important to know the following: intensity and volume of training, sequence of exercises, number of repetitions, sets, tempo of movement, rest time between sets, and type of exercise (Ralston et al, 2018), Weight training with short (60 seconds or less) and long (more than 60 seconds) rest intervals can help in training muscle strength (Grgic et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Learning motivation is recognized as one of the key factors that influence student success and achievement in the learning process. Learning motivation is the dominant factor that influences PE learning outcomes (Firdaus et al, 2023). Teaching strategies through structured tasks are the strongest predictor of motivation (Weeldenburg et al, 2022).…”
Section: Introductionmentioning
confidence: 99%